2018
DOI: 10.1080/08964289.2018.1432552
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mental Health and Substance use Treatment Needs of Commercially Sexually Exploited Youth Participating in a Specialty Juvenile Court

Abstract: The study sought to: 1) describe the mental health and substance use profiles among participants of a specialty trafficking court program (the Succeed Though Achievement and Resilience Court); 2) describe youths’ mental health and substance use treatment prior to participating in the program; and 3) examine whether abuse influences report of mental health problems and/or substance use. Retrospective case review of court files was performed on commercially sexually exploited youth who volunteered to participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Adverse childhood experiences are common among sex trafficked youth (Naramore, Bright, Epps, & Hardt, 2017 ). One study of trafficked youth participating in a specialty court reported that 92% of the sample had a child abuse report investigated and substantiated by child protective services (Cook, Barnert, Ijadi-Maghsoodi, Ports, & Bath, 2018 ). Several studies of justice-involved youth investigate differences in adverse childhood experiences between those who had been trafficked versus those who had not been trafficked and found that those who had been trafficked had higher odds of physical and sexual abuse, higher odds of emotional and physical neglect as well as family violence, compared to those with no trafficking history (Cole, Sprang, Lee, & Cohen, 2014 ; Reid, Baglivio, Piquero, Greenwald, & Epps, 2017 ; Wilson & Widom, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse childhood experiences are common among sex trafficked youth (Naramore, Bright, Epps, & Hardt, 2017 ). One study of trafficked youth participating in a specialty court reported that 92% of the sample had a child abuse report investigated and substantiated by child protective services (Cook, Barnert, Ijadi-Maghsoodi, Ports, & Bath, 2018 ). Several studies of justice-involved youth investigate differences in adverse childhood experiences between those who had been trafficked versus those who had not been trafficked and found that those who had been trafficked had higher odds of physical and sexual abuse, higher odds of emotional and physical neglect as well as family violence, compared to those with no trafficking history (Cole, Sprang, Lee, & Cohen, 2014 ; Reid, Baglivio, Piquero, Greenwald, & Epps, 2017 ; Wilson & Widom, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent court appearances are an indication of active program engagement. Additional details about the program and participants is published elsewhere (Cook et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research team members had several large group meetings to derive analytic categories from the data and develop an initial codebook of themes. The codebook was refined using iterative thematic analysis as guided by Charmaz's (2014) work in constructivist grounded theory. Once the team reached consensus about the codebook, a two-member team coded each interview transcript independently using a collaborative platform, Dedoose software (Version 8.1.14, Manhattan Beach, CA, USA).…”
Section: Discussionmentioning
confidence: 99%
“…When these risk factors are identified, they can be addressed in a timely way in an effort to prevent or interrupt the progression to human trafficking. These risk factors include having a history of childhood abuse [ 7 8 ]; a history of systems involvement in child welfare, including foster care [ 8 ]; having unstable living situations, being homeless, or having a history of running away [ 9 ]; use of alcohol and other drugs [ 10 ]; a history of mental health needs, including suicidality [ 7 11 ]; or identifying as LGBTQ [ 8 12 ]. All of these risk factors are assessed in the SBHC, and the mental health staff play a key role in providing not only counseling, but also assisting with referrals for concrete services.…”
Section: Reflectionsmentioning
confidence: 99%